2019
DOI: 10.1007/s13197-018-3552-9
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of texturised soy protein and yeast on the instrumental and sensory quality of hybrid beef meatballs

Abstract: The study aimed to investigate the effect of introducing texturized soy protein (TSP) at different levels (15% and 30%) with and without nutritional yeast as flavour enhancer on the sensory and instrumental quality of beef meatballs, compared to a soy and yeast-free control. Proximate analysis, colour, instrumental texture, cook loss, and sensory quality were investigated. Sixty participants assessed the samples using Check-all-that-apply (CATA) questions and hedonic scales. Overall, the texture of all TSP-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 26 publications
3
23
0
Order By: Relevance
“…Texture analysis of cooked sausage sample was carried out using circular platen probe P/75 mm diameter equipped with 30 kg load—Texture analyzer (Stable microsystem Texture Analyzer HD Plus model, England) as followed by Grasso et al. (2019). The sample was compressed twice for 1 mm and determined for its hardness, adhesiveness, resilience, cohesion, gumminess, springiness, and chewiness.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Texture analysis of cooked sausage sample was carried out using circular platen probe P/75 mm diameter equipped with 30 kg load—Texture analyzer (Stable microsystem Texture Analyzer HD Plus model, England) as followed by Grasso et al. (2019). The sample was compressed twice for 1 mm and determined for its hardness, adhesiveness, resilience, cohesion, gumminess, springiness, and chewiness.…”
Section: Methodsmentioning
confidence: 99%
“…Breadfruit chicken patties have higher sensory significance than jackfruit chicken patties Kamani et al (2019). made sausage with partial and complete replacement of meat with plant-proteins like soy and wheat which received high acceptance and had a good texture Grasso et al (2019). combined yeast and found that meatballs with 15% textured soy protein added had the best overall flavor and acceptance.…”
mentioning
confidence: 99%
“…These findings reveal that maintaining a high sodium level in meat analogs is important for consumer acceptance in terms of flavor, although this may lower the nutritional quality of the final product. In another study, Grasso et al [ 37 ] developed four types of hybrid meatballs by substituting 15% and 30% of beef with TSP in duplicates, with or without nutritional yeast, which was used as a flavor enhancer for its strong umami flavor. Sixty participants evaluated the four samples and an all-beef control by assessing degree of liking on a 9-point scale in terms of flavor, texture, and overall acceptance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hybrid meat products could open new business opportunities for the food industry [11], and indeed very recently, hybrid meat products have started appearing in the UK market [12]. The meat industry might be answering the growing flexitarian consumer needs, but the launch of hybrid meat products might also be representing a moment for change and an attempt from meat manufacturers to gain additional market share over new popular plant-based alternative protein sources [8].…”
Section: Introductionmentioning
confidence: 99%
“…Several research articles have shown that although challenging, it is technologically feasible to manufacture hybrid meat products such as burgers, meatballs and sausages with acceptable sensory quality [10,11,18,19]. However, consumer attitudes towards hybrid meat products have been investigated in a limited number of studies [8].…”
Section: Introductionmentioning
confidence: 99%